In vitro and in silico screening of Klebsiella pneumoniae new Delhi metallo-β-lactamase-1 inhibitors from endophytic Streptomyces spp. Issue 24 (26th December 2022) - Cheepurupalli, Lalitha; Diaz, Aathithya; Gopal, Adithya Conjeevaram; Rathore, Sudarshan Singh; Ramakrishnan, Vigneshwar; Ramakrishnan, Jayapradha
Abstract: The increase in drug resistance over the last two decades is a big threat in health care settings. More importantly, the dissemination of carbapenem-resistant Enterobacteriaceae is the major threat to public health with an increase in morbidity and mortality. β-lactamase is known to confer enteric bacteria with nearly complete resistance to all β-lactam antibiotics including the late-generation carbapenems. The commercially available β-lactamase inhibitors, clavulanic acid, sulbactam, and tazobactam are being met with an increasing number of resistant phenotypes and are ineffective against pathogens harbouring New Delhi metallo- β -lactamase (NDM-1). Inhibition of New Delhi metallo- β -lactamase-1 activity is one potential way to treat metallo β-lactamase (MBL) producing multi drug resistant (MDR) pathogen. The present study focused on screening of Klebsiella pneumoniae New Delhi metallo- β -lactamase-1 (BLIs) from endophytic Streptomyces spp. using in vitro and in silico methods. The study identified three potential inhibitors of New Delhi metallo- β -lactamase-1, namely dodecanoic acid, dl -alanyl- l -leucine and phenyl propanedioic acid. These molecules were found to bind to other MBLs namely, IMP-1 and VIM-2. To the best of our knowledge, this is the first kind of study reporting the binding mode of these molecules with New Delhi metallo- β -lactamase-1. Communicated by Ramaswamy H. Sarma